2008
DOI: 10.1002/ar.20722
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Fibroblast‐Like Synoviocyte Apoptosis Induced by Recombinant Human Endostatin in Rats with Adjuvant Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by pronounced synovial hyperplasia, in which there may be an imbalance between the growth and death of fibroblast-like synoviocytes (FLS). The present study was undertaken to examine the effect of recombinant human endostatin (rhEndostatin) on FLS apoptosis in experimental RA. Adjuvant arthritis (AA) was induced in male Sprague Dawley (SD) rats. Using cultured AA FLS obtained from these rats, the apoptosis process was measured by termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…24 Adjuvant-Induced Arthritis (AIA) was used as model for evaluation, because it is a well established model for experimental rheumatoid arthritis, which has many similar features with RA of human, like genetic linkage, synovial CD4+ cells and T cell dependence. [25][26] In present study, the significant difference in arthritis score between treated groups and negative control can only be seen within the administration period (day [14][15][16][17][18][19][20]. After administration period (day 21-28) arthritis score of middle and high dosage of RH-1402 are generally lower than that of negative control.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…24 Adjuvant-Induced Arthritis (AIA) was used as model for evaluation, because it is a well established model for experimental rheumatoid arthritis, which has many similar features with RA of human, like genetic linkage, synovial CD4+ cells and T cell dependence. [25][26] In present study, the significant difference in arthritis score between treated groups and negative control can only be seen within the administration period (day [14][15][16][17][18][19][20]. After administration period (day 21-28) arthritis score of middle and high dosage of RH-1402 are generally lower than that of negative control.…”
Section: Discussionmentioning
confidence: 67%
“…15 Arthritis was characterized by the first signs of redness or swelling of the ankle joints, which was observed at 10-12 days after the immunization.…”
Section: Induction Of Aamentioning
confidence: 99%
“…VEGF is a endothelial-cell-specific angiogenic factor and the best characterized system in the regulation of RA by angiogenesis. In addition, VEGF can act as a direct proinflammatory mediator during the pathogenesis of RA, and inhibition of rheumatoid synoviocytes apoptosis, which contributes to synovial hyperplasia [7,20]. In this study, we first identified a novel mechanism for antiangiogenesis in AA involving rhEndostatin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the functionality of endostatin has been demonstrated in vivo by its ability to induce regression of synovial proliferation of severe combined immunodeficiency (SCID) mice grafted from human rheumatoid arthritis [6]. Previous studies have indicated that administration of endostatin had an arthritis inhibiting effect in RA animal models [7]. These reports suggest that rhEndostatin can be considered as a potential therapeutic agent for RA.…”
Section: Introductionmentioning
confidence: 97%
“…FLS was prepared by the method of tissue explant cultivation as described (Huang et al, 2008). Fresh synovial membranes obtained from the knee joints of rats were minced, incubated in a fl atbottomed culture bottle and maintained in RPMI 1640 containing 15% fetal bovine serum (FBS) at 37°C, 5% CO 2 for 7 days.…”
Section: Animalsmentioning
confidence: 99%